Cooperative agreement between countries of the North Atlantic Ocean reduces marine plastic pollution but with unequal economic benefits - Beaumont, Nicola J.; Börger, Tobias; Clark, James R.; Hanley, Nick; Johnston, Robert J.; Meginnis, Keila; Stapenhurst, Christopher; de Vries, Frans P. (Communications earth & environment, 2025)
Plastic pollution in the world’s oceans threatens ecosystems and biodiversity. The connected nature of the marine environment suggests that coordinated actions by countries sharing an ocean border may provide more effective pollution control than unilateral actions by any one country. However, countries often fail to cooperate, even when joint economic benefits would be higher under cooperation. Here we present a modelling framework to determine the potential economic benefits of cooperative marine plastic pollution management. The framework integrates an estimated plastic transfer matrix from a particle tracking model with game theory to derive the economic benefits of international cooperation for 16 countries bordering the North Atlantic Ocean. Subject to modelling uncertainties, a fully cooperative agreement yields aggregate annual net benefits of around $36 billion and a 64% reduction in emissions. The net benefits of cooperation persist over alternative scenarios and considering the impact of uncertainties but vary in magnitude and distribution. Failure of countries to develop cooperative solutions through international agreements increases marine plastic pollution in the North Atlantic Ocean, leading to a significant loss of aggregate economic benefits, according to a game-theoretic integrated assessment model.